Chemical and Free Fatty Acid Composition of Goat Milk cheese Ripened with Lactobacillus acidophilusand Extract Rabbit Stomach as Coagulant - Nurliyani, Nurliyani; Astuti, Sulvia Dwi; Indratiningsih, Indratiningsih (2014)
-